Football and Web: Lexical Analysis of a Genre through Time - Rodrigo Esteves de Lima-Lopes (Papéis: Revista do Programa de Pós-Graduação em Estudos de Linguagens - UFMS, 2020)
This article aims to study the lexical choices in a set of news published by the British newspaper The Guardian. I seek to discuss whether there was a transformation in lexical choices in sports news articles published during the last five World Cups. This research is motivated by the fact that there is plenty of research in the field of multimodality that explore such transformation. However, little is discussed if the change in the newspaper's technological environment has also affected the lexical choices within this media. Data were collected from the newspaper's API, based on the World Cup dates between 2002 and 2018. The corpora are representative of the sports news genre within the context of the newspaper studied since the script collected all articles in the period. Analysis and data collection were performed using scripts written in R programming language. Wordlists were processed by statistical relevance, cluster dendrograms and co-occurrence networks in each of the text groups. Examples were obtained employing concordancers, also using the R language. The results show consistency amongst the corpora of the five World Cups, with room for some contextual variation that does not influence the definition of the genre. An initial conclusion is that, at least in the publication and genre studied, the transposition to the Internet has not caused a change in lexical choices.